Offshore wind installation vessels – A comparative assessment for UK offshore rounds 1 and 2. (15th January 2018) - Paterson, J.; D'Amico, F.; Thies, P.R.; Kurt, R.E.; Harrison, G.
Abstract: Marine operations play a pivotal role throughout all phases of a wind farm's life cycle. In particular uncertainties associated with offshore installations can extend construction schedules and increase the capital expenditure (CAPEX) required for a given project. Installation costs typically account for approximately 30% of the overall project cost. This study considers the installation modelling for UK offshore Wind Rounds 1 and 2 using probabilistic simulation tool. The tool is used to output time-domain predictions for the completion of key installation phases. By varying key wind farm characteristics such as distance to shore and the number of turbines, an assessment of vessel performance was completed for each round by reviewing recorded durations predicted by the software. The results provide a quantification of installation vessel performance and the associated deviations present a measure of installation risk. It is identified that the Round 1 vessels experience less weather downtime but higher variability and the Round 2 vessels perform more consistently but experience larger delays. The paper provides a structured method to identify and benchmark offshore wind installation risks, to support developers and project planners. Abstract : Highlights: Round 2 vessel have greater weather downtime compared to Round 1. Round 1 vessels exhibit greater installation risk. The paper provides a structured method to identify and benchmark offshore wind installation risks.